Association of chalamydia trachomitis infection in patients with tubal factor infertility - Banu, Jesmine; Das, Shakti; Fatima, Parveen; Sultana, Rozi (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: chalamydia trachomitis; infertility; tubal factor doi: 10.3329/jcmcta.v19i1.3842 Journal of Chittagong Medical College Teachers' Association 2008: 19(1):4-7